On Literary and Other Texts (KULT_online, 2011)
This volume contains selected studies by medievalist Jan-Dirk Müller that examine vernacular literary texts of the Middle Ages and the Early Modern Age, which are here understood as a medium for the reflection of cultural configurations. The essays deal with the possibilities and problems of mediaeval studies from a cultural studies perspective, and cover a wide spectrum of texts from the 12th to the 16th centuries, focusing on their concepts of cultural systems, the interaction between 'text' and culture in mediaeval society, the discussion and transformation of social norms, and the relation between myths and rituals.